2016
DOI: 10.1073/pnas.1607931113
|View full text |Cite
|
Sign up to set email alerts
|

Human antibody responses after dengue virus infection are highly cross-reactive to Zika virus

Abstract: Zika virus (ZIKV) is an emerging mosquito-borne flavivirus of significant public health concern. ZIKV shares a high degree of sequence and structural homology compared with other flaviviruses, including dengue virus (DENV), resulting in immunological cross-reactivity. Improving our current understanding of the extent and characteristics of this immunological cross-reactivity is important, as ZIKV is presently circulating in areas that are highly endemic for dengue. To assess the magnitude and functional qualit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

23
492
3
16

Year Published

2017
2017
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 509 publications
(534 citation statements)
references
References 39 publications
23
492
3
16
Order By: Relevance
“…One factor that may have affected the data from Rio de Janeiro is that almost 90% of those women were serologically positive for Dengue (DENV), presumably due to past infections with one or more of the known DENV strains (DENV1-4). Sero-crossreactivity between DENV1-4 and ZIKV (18,19) may allow the latter to be piggybacked across the protective STB layer of the mature villous placenta. Such transcytosis of maternal IgG appears to be initiated around the beginning of the second trimester and continues to term (20).…”
mentioning
confidence: 99%
“…One factor that may have affected the data from Rio de Janeiro is that almost 90% of those women were serologically positive for Dengue (DENV), presumably due to past infections with one or more of the known DENV strains (DENV1-4). Sero-crossreactivity between DENV1-4 and ZIKV (18,19) may allow the latter to be piggybacked across the protective STB layer of the mature villous placenta. Such transcytosis of maternal IgG appears to be initiated around the beginning of the second trimester and continues to term (20).…”
mentioning
confidence: 99%
“…Preclinical studies have demonstrated a protective role of CD8 T cells and antibodies against ZIKV infection, the latter being sufficient for complete protection [67][68][69][70]. However, cocirculation of DENV, WNV and ZIKV has been reported in several countries and previous studies suggested an immunological cross-reactivity between viruses, which may drive immune-mediated enhancement [71][72][73]. This hypothesis was recently confirmed in mice demonstrating that DENV or WNV specific antibodies are cross-reactive to ZIKV and enhance disease severity in whole organisms [74].…”
Section: Zika Virusmentioning
confidence: 99%
“…Several reports have now explored this possibility 21,22,35,36 , showing that serum from dengue immune donors strongly binds to ZIKV by ELISA. While most of these sera are non-neutralizing of ZIKV some anti-dengue serum samples showed quite respectable neutralization of ZIKV (FRNT50 <1in200) 21,35 . However, although most anti-DENV serum samples fail to neutralize ZIKV they potently promote ADE of ZIKV in vitro.…”
Section: Dengue and Zika Interactionsmentioning
confidence: 99%
“…Analysis of panels of monoclonal antibodies made from DENV or ZIKV infected donors have now been reported 12,18,22,35,37,38,39,40 . These mAb show substantial crossreaction between DENV and ZIKV suggesting that ZIKV could be considered as a fifth member of the DENV serocomplex.…”
Section: Dengue and Zika Interactionsmentioning
confidence: 99%